Molecular phylogenetic relationship of Toxocara canis isolated from dogs in Phu Tho province, Vietnam - Quyen, Nguyen Thi; Kim Lan, Nguyen Thi; Doanh, Pham Ngoc (Academia Journal of Biology, 2016)
Dog roundworms include some species of the genera Toxocara and Toxascaris. Of these, Toxocara canis distributes globally and can infect humans to cause a number of clinical manifestations, such as visceral larva migrans, ocular larva migrans, eosinophilic meningoencephalitis, and neurotoxocariasis. In Vietnam, human cases infected with Toxocaris larvae have recently been reported at relatively high infection rates. It becomes interested by scientists to conduct epidemiological surveys. However, most studies focused on morphology and epidemiology, there has been very little research at molecular level. In this study we analyzed ITS2 and CO1 sequences, and evolutionary relationships of dog roundworms obtained from Phu Tho province. The results clearly confirmed that they are T. canis. The isolates from Phu Tho province showed high genetic identities and phylogenetically closely related to the isolates from Guangdong, China. The ITS2 and CO1 sequences of T. canis greatly differ from those of other Toxocara species and Ta. leonina, indicating these genes as good markers to distinguish dog roundworms at species level.